2021
DOI: 10.3389/fmicb.2021.616956
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Processes and Co-occurrence Patterns of Abundant and Rare Bacterial Community in the Eastern Indian Ocean

Abstract: Microbial communities are composed of many rare species and a few abundant species. Considering the disproportionate importance of rare species for ecosystem functioning, it is important to understand the mechanisms structuring the rare and abundant components of a diverse community in response to environmental changes. Here, we used a 16S ribosomal RNA gene sequencing approach to investigate the bacterial community diversity in the Eastern Indian Ocean (EIO) during the monsoon and intermonsoon. We employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 91 publications
2
14
0
Order By: Relevance
“…Sea surface temperature and salinity were determined and recorded using a conductivity–temperature–depth (CTD) system on board (Seabird SBE 911Plus, Sea-Bird Electronics, WA, United States). Sample analysis for other physicochemical parameters, such as inorganic nutrients and Chlorophyll a (Chl a ), were consistent with our previous work ( Wu et al, 2019 ; Li et al, 2021b ). Briefly, we used 100-ml PE bottles to collect seawater for nutrient analysis.…”
Section: Methodssupporting
confidence: 89%
“…Sea surface temperature and salinity were determined and recorded using a conductivity–temperature–depth (CTD) system on board (Seabird SBE 911Plus, Sea-Bird Electronics, WA, United States). Sample analysis for other physicochemical parameters, such as inorganic nutrients and Chlorophyll a (Chl a ), were consistent with our previous work ( Wu et al, 2019 ; Li et al, 2021b ). Briefly, we used 100-ml PE bottles to collect seawater for nutrient analysis.…”
Section: Methodssupporting
confidence: 89%
“…By constructing the linkage between assembly processes and species co-occurrence in microbial communities, Jiao et al (2020) found that the microbial co-occurrences tended to be higher when agricultural soil microbial communities were mainly driven by dispersal limitation. By contrast, Li et al (2021a) found that deterministic processes (mainly heterogeneous selection) became a less dominant ecological process in the intermonsoon communities in the Eastern Indian Ocean as the co-occurrence increased. These linkages were thought to be largely related to environmental filtering ( Jiao et al, 2020 ; Li et al, 2021a ).…”
Section: Discussionmentioning
confidence: 78%
“…By contrast, Li et al (2021a) found that deterministic processes (mainly heterogeneous selection) became a less dominant ecological process in the intermonsoon communities in the Eastern Indian Ocean as the co-occurrence increased. These linkages were thought to be largely related to environmental filtering ( Jiao et al, 2020 ; Li et al, 2021a ). In this study, an opposite trend was observed that stochastic processes become less dominant as the connection of microbial communities increased.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations